OPTIMALISASI DIVERSIFIKASI CABANG USAHATANI TANAMAN SAYURAN DI KELURAHAN ANDAI DISTRIK MANOKWARI SELATAN KABUPATEN MANOKWARI - Rosia Talenta Siagian; Diana N. Irbayanti; Maria I. Arim (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
Optimizing Diversification is an effort to optimize the income from various types of farming activities carried out. This study aims to (1) Identify the types of vegetables cultivated by farmers in Andai Village, South Manokwari District for one year (2) Calculate the income generated from each type of vegetable plant that is cultivated in one year (3) Know the maximum income that is produced from these types of vegetables. The method used in this research is descriptive method through a case study approach. The data in this study were analyzed using tabulation and linear programming analysis by using the simplex method to determine the area of land, work flow and optimal capital devoted to the types of vegetables cultivated that can provide optimum income. Based on the results of the analysis obtained 8 types of vegetable plants cultivated by farmers in Andai village for one year. Maximum income for the types of vegetables cultivated for one year is found in kale, spinach and chili binoculars.